EXTH-33. RECEPTOR PHARMACOLOGY OF ONC201: THE FIRST BITOPIC DRD2 ANTAGONIST FOR CLINICAL NEURO-ONCOLOGY. (11th November 2019) - Benjamin Free, R; Cuoco, Caroline; Prabhu, Varun; Willette, Blair; Day, Marilyn; Anantharaman, Lakshmi; Sulli, Chidananda; Davidson, Edgar; Deacon, Sean; Rucker, Joseph; Charter, Neil; Doranz, Benjamin; et al.
Abstract: ONC201 has exhibited durable tumor regressions in midline high grade glioma patients. G protein-coupled receptor (GPCR) dopamine receptor D2 (DRD2) is overexpressed in high grade gliomas, controls several oncogenic mechanisms, and its antagonism causes tumor cell apoptosis. Using bioinformatic and GPCR screens, we previously demonstrated selective DRD2/3 antagonism by ONC201 at therapeutic concentrations that translates into a wide therapeutic window, unlike antipsychotics that also target other dopamine receptors and GPCRs (Prabhu et al. CCR 2019 and Madhukar et al. Nat Comm in press). Here, we identify hallmarks of non-competitive DRD2 antagonism by ONC201 in β-arrestin, cAMP and radioligand competition assays. ONC201 caused both a shift in the IC50 and repression of Emax in the dopamine-dose-response curves for DRD2. Schild analysis and fitting these data to an operational model of allostery were consistent with non-competitive antagonism. Alanine scanning mutagenesis of DRD2 identified 6 orthosteric and allosteric residues that are critical for ONC201-mediated antagonism. The residues identified were predominantly conserved in DRD2/3 and were not relevant for antagonism by antipsychotics further explaining the unique selectivity of ONC201. Molecular docking revealed orthosteric interactions at TM-II and an extended binding pocket into an allosteric site. Other critical residues were clustered at an allosteric area at the interface of TM-IV and –V that has been shown to mediate the DRD2 homodimer interface. Point mutations at either site decreased the affinity of ONC201 in competition assays with radiolabeled methyl-spiperone, suggesting cooperativity between these topographically distinct sites. In summary, ONC201 causes a mixed non-competitive and competitive antagonism of DRD2 consistent with a bitopic mechanism of action that may explain its unique selectivity, safety, and anti-cancer activity in clinical trials as the first compound to target this receptor for clinical neuro-oncology. Non-competitive DRD2 antagonism may be critical for ONC201 anti-tumor efficacy in dopamine-rich microenvironments such as midline gliomas.